2004
DOI: 10.1002/adem.200400102
|View full text |Cite
|
Sign up to set email alerts
|

Processing and Characterization of Al‐Cu and Al‐Mg Base Composites Reinforced with TiC

Abstract: elements will contain diamond cutting plates since preliminary studies carried out at MTU Aero Engines proofed that this material shows practically no attrition when cutting the fibers.Laser cutting does not lead to a proper cutting surface. This process is therefore not suitable for further application. Together with laser cutting a so called ªonion-structureº was observed on the pyrolithic carbon coating of SiC fibers, which leads additionally to a fiber destruction at the interface SiC to Titanium coating. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…They obtained contact angles around 126 • , 115 • , and 105 • for 1100, 1130, and 1170 • C. More recently, Zarrinfar et al [14] reported poor wetting between molten copper and TiC which makes difficult to produce copper based ceramics composites. However, in previous work was reported the fabrication of Al-Cu alloys/TiC composites processed by the pressureless infiltration technique at temperatures of 900 and 1000 • C [17]. The poor wettability is attributed to the stable electron configuration of copper which has a full "3d" orbital.…”
Section: Wetting and Spreading Kineticmentioning
confidence: 96%
“…They obtained contact angles around 126 • , 115 • , and 105 • for 1100, 1130, and 1170 • C. More recently, Zarrinfar et al [14] reported poor wetting between molten copper and TiC which makes difficult to produce copper based ceramics composites. However, in previous work was reported the fabrication of Al-Cu alloys/TiC composites processed by the pressureless infiltration technique at temperatures of 900 and 1000 • C [17]. The poor wettability is attributed to the stable electron configuration of copper which has a full "3d" orbital.…”
Section: Wetting and Spreading Kineticmentioning
confidence: 96%
“…In addition, in the EDS results, the polygonal and pellicle shapes shown in Figures 4 and 5(a) consist of the Ti and Al atoms, respectively. 12 It is verified that the Al precursor coated on the TiC particle becomes the amorphous Al 2 O 3 after heat treatment at 500 C. …”
Section: Resultsmentioning
confidence: 96%
“…These MMCs have been displacing to the commercial steels, mainly when specifi c properties are needed [ 1 ]. The greatest diffi culty in the composite manufacture at liquid state is the wettability of the ceramic phase on the liquid metals [ 2 ]. According to this fact, it is important to improve the wettability in order to get a good junction between the metallic matrix and the ceramic [ 3 ].…”
Section: Introductionmentioning
confidence: 99%